Hypersonic nonequilibrium flows : fundamentals and recent advances - Josyula, Eswar (Progress in astronautics and aeronautics ;, 2015)
This book provides an overview of the recent developments in precision aerial cargo delivery from the standpoint of developing guidance, navigation and control (GNC) algorithms for the self-guided parafoil and parachute-based aerial delivery systems (PADS). Developing a robust GNC system involves aerodynamics modeling, structural and parametric system identification, understanding the environment PADS glides through developing and testing suitable navigation solutions, guidance strategies, and controllers. --